الذات في مواجهة السرطان لاوعي النص في سيرة حسين البرغوثي "سأكون بين اللوز" / The Self in Facing Cancer: Text Unconsciousness in the Biography of Hussein Barghoutsī "I Will Be Among the Almonds" - Abdurraḥman Idris Aldrees, Huda (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2021)
مُلخَّص البحث: يقف هذا البحث أمام السيرة الذاتية لحسين البرغوثي سأكون بين اللوز، نظرا لأنها تجسّد حالة استثنائية في مواجهة الذات لمرض السرطان، وتحمل كثيراً من الرؤى والتصورات حول هذا المرض، وآثاره وانعكاساته على المريض، وطرق علاجه، ويهدف إلى استنطاق لاوعي هذه السيرة من منظور التحليل النفسي النصي، وسأقوم فيه برصد رحلة مريض السرطان منذ لحظة اكتشافه، إلى لحظة وصوله لحالة الاستبصار والمواجهة، لأبيّن كيف يمكن أن يكون الإبداع السردي وسيلة لمقاومة المرض وعلاجه، ومواجهة الفناء الجسدي لدى المبدع، بخطاب سردي مكثف، يغوص ويستبطن، ويكشف أعماق الذات منطلقا من أعماق النص؛ للخروج من إطار هذه التجربة الذاتية إلى تجسيد نموذج إنساني لمريض السرطان؛ توصل البحث إلى نتيجة جوهرية هي إمكانية استثمار الممارسين الصحيين للنصوص السردية الإبداعية- وبخاصة السيرة الذاتية بكل تجلياتها- للكشف عن معاناة المرضى، ومعرفة احتياجاتهم النفسية والجسدية في هذه الرحلة الطويلة المليئة بالآلام، ووضع أيديهم على الإشكالات التي قد تؤثر سلبا في خطة العلاج. الكلمات المفتاحية: العلاج بالسرد، مواجهة السرطان، لاوعي النص، التداعي الحر. Abstract: This paper highlights on the autobiography of Hussein Barghoutsī (I Will Be Among the Almonds) as it embodies an exceptional case of cancer self-confrontation. It also bears many visions and perceptions about this disease, its effects on the patient, and its methods of treatment. The objective of the paper is to uncover the subconscious of this biography from the perspective of textual psychoanalysis, and to examine the subconscious of the text and monitor the journey of a cancer patient from the beginning of its discovery, fore sighting until its confrontation. This is to show how narrative creativity can be a means of resisting disease and treating it and challenge the physical mortality of the creative person through an intensive narrative discourse, which explores the depths of the self, starting from the depths of the text. This research concludes with the possibility of health practitioners utilizing creative narrative texts, especially autobiographies, to reveal the suffering of patients, know their psychological and physical needs in this long, painful journey, and distinguish issues that may negatively affect the treatment plan. Keywords: Narrative therapy, fighting cancer, text unconsciousness, free association. Abstrak: Kajian ini menbicarakan autobiografi Hussein Barghoutsī (Aku hanya akan berada dalam kalangan almond) kerana ia menonjolkan konfrontasi diri dengan kanser dalam keadaan yang luar biasa. Ia juga mempunyai banyak sudut pandangan dan persepsi tentang penyakit ini, kesannya kepada pesakit, dan kaedah rawatannya. Objektif kajian ini adalah untuk mendedahkan dimensi alam bawah sedar biografi ini dari perspektif psikoanalisis tekstual. Ia juga bertujuan untuk menulusuri alam bawah sedar teks dan memantau perjalanan pesakit kanser dari permulaannya mengetahui tentang penyakit itu, pandangannya yang jauh serta janggkaannya, dan detik-detik konforntasinya melawan pesakit tersebut. Kajian ini juga ingin menunjukkan bagaimana kreativiti naratif boleh menjadi cara untuk menentang penyakit dan merawatnya dan mencabar kematian fizikal pengidapnya melalui wacana naratif yang intensif, yang meneroka kedalaman diri, yang difahami daripada kedalaman maksud teks. Penyelidikan ini diakhiri dengan kemungkinan untuk pengamal kesihatan menggunakan teks naratif kreatif, terutamanya autobiografi, untuk mendedahkan penderitaan pesakit, mengetahui keperluan psikologi dan fizikal mereka dalam perjalanan yang panjang dan menyakitkan ini, dan menghindarkan isu-isu negatif yang boleh menjejaskan rancangan rawatan. Kata kunci: Terapi naratif, memerangi kanser, pra sedar teks, pergaulan bebas.